$${{ρ }}$$ ρ exchange contribution to neutrinoless double beta decay - Namit Mahajan (European Physical Journal C: Particles and Fields, 2023)
Abstract We consider $$ρ $$ ρ meson contributions to neutrinoless double beta decay amplitude stemming from the hadronization of the short distance quark-electron currents. These contributions are evaluated within vacuum dominance approximation. The one and two $$ρ $$ ρ exchange contributions affect the Fermi transition nuclear matrix element in a way that lead to near cancellations in the same chirality, left–left and right–right, short range amplitudes when these new contributions are combined with the conventional short range amplitudes, while the left–right amplitude almost triples. A rough estimate comparing this contribution to the long range pion exchange contribution indicates that $$ρ $$ ρ exchange contribution can easily be $$\mathcal {O}(10%)$$ O ( 10 % ) of the pion contribution. When considering precision predictions, $$ρ $$ ρ exchange amplitudes should be included in any phenomenological study, like in left–right theories.